2021
DOI: 10.3389/fgeed.2021.745559
|View full text |Cite
|
Sign up to set email alerts
|

The Application of CRISPR/Cas Systems for Antiviral Therapy

Abstract: As CRISPR/Cas systems have been refined over time, there has been an effort to apply them to real world problems, such as developing sequence-targeted antiviral therapies. Viruses pose a major threat to humans and new tools are urgently needed to combat these rapidly mutating pathogens. Importantly, a variety of CRISPR systems have the potential to directly cleave DNA and RNA viral genomes, in a targeted and easily-adaptable manner, thus preventing or treating infections. This perspective article highlights re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…T7E1 and SURVEYOR enzymes can cut these fragments. This cut can be detected on the agarose gel [93,94]. Another method of indel mutation detection is using a high-resolution melting curve (HRM), which can be used to identify heteroduplex DNA mismatches.…”
Section: Knock-out Detection Methodsmentioning
confidence: 99%
“…T7E1 and SURVEYOR enzymes can cut these fragments. This cut can be detected on the agarose gel [93,94]. Another method of indel mutation detection is using a high-resolution melting curve (HRM), which can be used to identify heteroduplex DNA mismatches.…”
Section: Knock-out Detection Methodsmentioning
confidence: 99%
“…The Cas9-, Cas12- (both cut dsDNA), and Cas13- (cuts ssRNA) based systems have been adapted for treatment of viral infections in vitro and in vivo in mammals (Fig. 1 c) [ 23 ]. For example, EBT-101 was a first-in-human one-time gene therapy against HIV with adeno-associated virus used to deliver the CRISPR/Cas9 system [ 24 ].…”
Section: Antiviral Agents and Therapiesmentioning
confidence: 99%
“…However, there is an urgent need to develop new methods to combat these pathogens. Being one of the most valued molecular tools, the CRISPR-Cas system is currently being used for developing antiviral strategies in various organisms [155][156][157]. Of all nucleases described in the specialized literature, it has been shown that different variants of Cas9, Cas12, and Cas13 exhibit the most promising results regarding the antiviral approaches [155].…”
Section: Applicability Of Crispr-cas In Anti-bmnpv Therapymentioning
confidence: 99%